Primary Total Hip Arthroplasty: Equivalent Outcomes in Low and High Functioning Patients. Issue 11 (November 2016) - Alzahrani, Mohammad Mesfer; Smith, Karen; Tanzer, Dylan; Tanzer, Michael
Abstract : Objective: Previous studies suggest that patients with poorer physical function prior to undergoing total hip arthroplasty (THA) have a lower postoperative functional outcome. We sought to determine if the preoperative level of function was predictive of the outcome in patients undergoing THA using modern perioperative protocols and surgical techniques. Methods: A prospective cohort study design evaluated the preoperative and 2-year postoperative health-related quality of life (HRQoL) scores of 200 patients who underwent THA. The cohort was divided into two groups according to the median preoperative Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) physical function scores. Results: Both high and low function groups had significant improvements in the HRQoL scores ( P < 0.001). However, this improvement was substantially greater in the low function group, resulting in no difference in the HRQoL outcomes of the two groups at final follow-up. Conclusion: This study contradicts the previously held belief that patients with worse function before THA do not do as well as those with less preoperative disability. Level of Evidence: Level II.